Injury with a Metal Cutting Wheel Involving Three Anatomical Regions of the Neck - Yeşilkuş, Furkan; Tuncel, Yusuf; Çağdaş Kumbul, Yusuf; Okur, Erdoğan; Atilla Ayyıldız, Veysel (ENT Updates, 2024)
Penetrating head and neck injuries are rare but life-threatening injuries. These injuries are classified into 3 regions in the neck. Injuries involving all 3 regions are almost absent in the literature. Appropriate personal protective equipment must be used to protect from such injuries. In this case report, a case remarkable for a foreign body causing injury is presented.